2014
DOI: 10.1186/1476-4598-13-114
|View full text |Cite
|
Sign up to set email alerts
|

Serum cytokine biomarker panels for discriminating pancreatic cancer from benign pancreatic disease

Abstract: BackgroundWe investigated whether combinations of serum cytokines, used with logistic disease predictor models, could facilitate the detection of pancreatic ductal adenocarcinoma (PDAC).MethodsThe serum levels of 27 cytokines were measured in 241 subjects, 127 with PDAC, 49 with chronic pancreatitis, 20 with benign biliary obstruction and 45 healthy controls. Samples were split randomly into independent training and test sets. Cytokine biomarker panels were selected by identifying the top performing cytokines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 45 publications
2
53
1
Order By: Relevance
“…Alternatively, we conducted the IPA and identified several molecules such as PDGFB and VEGFA resulting from the net effects of differentially expressed miRNAs in AIP. Previous studies have shown that serum PDGF-BB and VEGF levels were altered in CP and pancreatic cancer [37,38,39], but PDGF-BB levels in patients with CP or pancreatic cancer were not different from those in controls in this study. Serum cytokine profiles in patients with AIP are currently unknown.…”
Section: Discussioncontrasting
confidence: 33%
“…Alternatively, we conducted the IPA and identified several molecules such as PDGFB and VEGFA resulting from the net effects of differentially expressed miRNAs in AIP. Previous studies have shown that serum PDGF-BB and VEGF levels were altered in CP and pancreatic cancer [37,38,39], but PDGF-BB levels in patients with CP or pancreatic cancer were not different from those in controls in this study. Serum cytokine profiles in patients with AIP are currently unknown.…”
Section: Discussioncontrasting
confidence: 33%
“…The utility of CA19-9 is limited in patients who are Lewis blood type negative (Lea -b -). Another limitation of CA 19-9 is that it can be falsely elevated in the presence of biliary obstruction [21]. CEA was the only serum glycoprotein used for diagnosing PC.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 is linked to both pancreatic cancer 18-20 and to fatigue and depression 16,19,21 . Elevated levels of IL-6 have been found to be associated with clinical depression in patients with other cancers 15,22,23,24 .…”
Section: Discussionmentioning
confidence: 99%